2020
DOI: 10.1101/2020.08.05.238774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially Explicit Modeling of Community Occupancy using Markov Random Field Models with Imperfect Observation: Mesocarnivores in Apostle Islands National Lakeshore

Abstract: We hereby developed a Markov random field based spatial-explicit community occupancy model that accounts for spatial auto-correlation and interspecific interactions in occupancy simultaneously while also account for interspecific interaction in detection. Simulation results showed the new model can distinguish different mechanisms. We applied this new model to camera trap data of Fisher(Pekania pennanti)-Marten(Martes americana) and Coyote(Canis latrans)-Fox(Vulpes vulpes) system in Apostle Island National Lak… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Furthermore, Allen et al (2019) found that marten presence on an island was determined by human avoidance and direct competition with larger carnivores (i.e., fisher) to a lesser degree, possibly explaining why martens were more likely to colonize islands further from the mainland. However, Shen et al (2021) found partitioning between martens and fishers to be mostly explained by their opposing source-sink dynamics, rather than direct competition. While more research is needed, island isolation likely has a more positive effect on the presence of sensitive species like marten than other carnivores, where more isolated islands provide refuge from mainland stressors (Allen et al, 2019;Shen et al, 2021;Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, Allen et al (2019) found that marten presence on an island was determined by human avoidance and direct competition with larger carnivores (i.e., fisher) to a lesser degree, possibly explaining why martens were more likely to colonize islands further from the mainland. However, Shen et al (2021) found partitioning between martens and fishers to be mostly explained by their opposing source-sink dynamics, rather than direct competition. While more research is needed, island isolation likely has a more positive effect on the presence of sensitive species like marten than other carnivores, where more isolated islands provide refuge from mainland stressors (Allen et al, 2019;Shen et al, 2021;Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…However, Shen et al (2021) found partitioning between martens and fishers to be mostly explained by their opposing source-sink dynamics, rather than direct competition. While more research is needed, island isolation likely has a more positive effect on the presence of sensitive species like marten than other carnivores, where more isolated islands provide refuge from mainland stressors (Allen et al, 2019;Shen et al, 2021;Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Other applications of random fields in biology include demography and selection to study weakly deleterious genetic variants in complex demographic environments [111] and for species clustering [112], in population genetics. MRFs have also been applied to understand species distribution patterns and endemism and to unveil [113] interactions between cooccurring species in processes governing community assembly [114]; as well as for spatially explicit community occupancy [115] in ecology.…”
Section: Applications Of Mrfs In Ecology and Other Areas Of Biologymentioning
confidence: 99%